Biomarkers of fibroproliferative healing in fibrosing idiopathic interstitial pneumonias - Koziar Vašáková, Martina; Šterclová, Martina; Stránská, Eliška; Manďáková, Petra; Skibová, Jelena; Matěj, Radoslav (The open respiratory medicine journal, 2012)
AIMS: The main feature of fibrosing idiopathic interstitial pneumonias (fIIPs) is the fibroproliferative potential of underlying pathogenetic process. We hypothesize that the concentration of potential markers of fibroproliferative healing, PAR-2, TGF-β1, TNF-α and IL-4Rα in bronchoalveolar lavage fluid (BALF) differ in patients with fIIPs compared to controls (C). PATIENTS AND METHODS: 10 patients with fIIPs and 9 controls (C) were included to the study. Concentrations of CD124 (IL4Rα), PAR-2, TGF-β1 and TNF-α in BALF were determined using the ELISA method. RESULTS: We observed higher concentrations of IL4Rα (fIIPS 1499.4 pg/ml vs C 255.5 pg/ml; p < 0.05), PAR-2 (fIIPS 1807.9 pg/ml vs C 421.0 pg/ml; p < 0.05) and TGF-β1(fIIPS 283.0 pg/ml vs C 197.1 pg/ml; p < 0.01) in BALF in fIIPs versus C. The values of TNF-a in BALF did not differ significantly in fIIPs compared to controls. The ratios also showed differences in fIIPS and C: IL4Rα/TGF-β1 (fIIPS 6.19 vs C 0.68; p = 0.0143); TNF-α/IL4Rα (fIIPS 0.84 vs C 7.93; p = 0.043); TGF-β1/TNF-α (fIIPS 0.21 vs C 0.16; p = 0.0179) and protein/PAR-2 (fIIPS 0.06 vs C 0.28; p = 0.0033). CONCLUSIONS: We found that PAR-2, TGF-β1 and IL-4Rα are significantly up-regulated in the BALF of fIIPs compared to controls, therefore we suppose they could become biomarkers of fibroproliferative healing.
Keywords: receptory interleukinu-4; Transforming Growth Factor beta; Idiopathic Interstitial Pneumonias; bronchoalveolární lavážní tekutina; IL4R.; Idiopathic interstitial pneumonias; PAR-2; TGF-beta; biomarkers; bronchoalveolar lavage fluid; fibroproliferative healing; lidé; Bronchoalveolar Lavage Fluid; Receptors, Interleukin-4; Idiopathic Pulmonary Fibrosis; idiopatické intersticiální pneumonie; receptor PAR-2; transformující růstový faktor beta; biologické markery; idiopatická plicní fibróza; Receptor, PAR-2; Biomarkers; Humans